Excavating the Horns’ Chamber Mustatil: A Neolithic open-air sanctuary evidencing pastoral nomadic ritual activity in northwestern Arabian Desert (AlUla) - Abu-Azizeh, Wael; Studer, Jacqueline; Alahmari, Saeed; Boyle, Angela; Dausse, Lucie; Quartermaine, Jamie; Strolin, Laura; Tombret, Olivier; Zazzo, Antoine (Proceedings of the Seminar for Arabian Studies, 2023)
As part of the large-scale archaeological landscape survey undertaken in AlUla County on behalf of the Royal Commission for AlUla (RCU), an excavation program focusing on the Late Prehistoric remains was launched to begin establishing chronology and function for the variety of site types evident in this region. Many of these Late Prehistoric site types remain enigmatic, as surface examination often does not allow a determination of their date and nature. These include the mustatil monuments (“rectangle” in Arabic), which have a distinctive, typically rectangular shape, reaching sometimes over 600 m in length, and constitutes some of the most impressive stone-built constructions of the landscape. The excavation at one of these sites, located on the fringe of the AlUla ‘Core Area’, revealed an exceptional structured deposit of faunal remains, of unusually high quantities of animal bones, exclusively of skull parts of wild and domesticated horned species. The deposit of the Horns’ Chamber Mustatil attests to complex and sophisticated ritual practices that date to the Neolithic period (ca. 5300-5000 cal BCE). This unprecedented discovery sheds a new light on ritual activities evidenced by a widespread Neolithic tradition of monumental open-air sanctuaries related to early pastoral nomadic societies in the northwestern Arabian Desert.